Roosting under pressure: cumulative tourist load negatively impacts colony activity in the rare bat Furipterus horrens - García-Valverde, Daniel; Alfaro-Lara, Henry; Vargas-Castro, Luis Esteban (Frontiers in Ethology, 2026)
Understanding bat activity in areas with human disturbance is increasingly important for their conservation. Bat colonies roosting on infrastructure used for tourism may be negatively affected over time, as tourism-related activities can disrupt roosting behavior, and affect colony size and stability. In this study, we evaluated the impact of tourist load on bat activity with passive acoustic monitoring in one Costa Rican eco-lodge, which hosts the only currently known colony of thumbless bats, Furipterus horrens, in the region. Their elusive behavior, limited survey records, and fragmented geographic distribution within the Neotropics, make them one of the least studied bat species. The colony we studied roosts under a series of bungalows used for tourist accommodation. We deployed an acoustic system composed of 19 recorders distributed under six bungalows, to monitor bat acoustic activity. Each bungalow was recorded for up to 43 nights in total, within five monitoring periods between February and April 2025. In addition, we conducted visual count surveys during each acoustic monitoring period. We gathered data on bungalow occupancy and analyzed the relationship between the cumulative reservation load of three and seven consecutive nights, on bat activity, using generalized linear mixed models. Our results show that for a given bungalow, higher bat acoustic activity significantly predicts higher abundance of individuals. Furthermore, even though acoustic activity was not affected by a three-night reservation load, the seven-night reservation load negatively affected the acoustic activity of thumbless bats, suggesting that this species is sensitive to an accumulated human disturbance over this period. These findings highlight the importance of adequate management plans that integrate people and bat populations, particularly in the context of high anthropogenic loads, like tourism-related activities in eco-lodges. Understanding these impacts provides critical information for making better-informed decisions that balance ecotourism with the conservation of vulnerable wildlife.